Guide to managerial communication effective business writing and speaking - Munter, Mary (Pearson Prentice Hall, 2005)
For undergraduate and MBA course in Management Communication, Writing, or Oral Presentations courses, and Executive Seminars or Workshops. Guide to Managerial Communication is a clear, concise and practical reference to effective written and oral communication in a managerial, business, government, or professional context.